A filosofia acadêmica: estudo histórico-crítico do ensino de filosofia na Universidade Federal do Rio de Janeiro - Martins, Angela Maria Souza (1985)
The course of philosophy at the Institute of Philosophy and Social Sciences of the Federal University of Rio de Janeiro was characterized, in the early seventies, mainly by a traditional, dogmatic and unhistorical approach, giving origin to bewilderment and lack of interest for the course among the student body. This approach, according to the opinion of teachers and students from former periods, was not peculiar to the seventies, but remained unchanged for some years of the course at that educational , establishment, bringing about, at some historic periods, the conflict between the official position of the course and the wishes and interests of the students. Taking the point of view that philosophy is not a theoretical, 'eternal', 'immutable' and unhistorical discourse, but rather mirrors changes and contradictions, what is sought through a historical approach - beginning with the colonial period through ta the sixties in the seventieth-century - is to find the causes that deter mine such dogmatism, such stanch opposition ta change and to historicism which are the characteristics of the course of philosophy at the Federal University of Rio de Janeiro. The background that was always born in mind was the historic course of the conflict between the official proposition for the tearing of philosophy and the wishes and interests of students, that is, their perspective for the study of philosophy. This conflict bears out the dichotomy being/thinking perpetuated by the approach to the study of philosophy within the Brazilian educational context.